Students’ Creativity in Solving Ill Structured Problem Context Calorie Intake - Antika, Helen Novi; Anjasari, Tika; Kohar, Ahmad Wachidul (Universitas Negeri Surabaya, 2022)
In math learning, creative thinking is very important because it allows broad thinking to find new solutions to problems. This study aims to describe the level of students' creative thinking in solving ill-structured problems in the context of calorie intake. This type of research was descriptive with a qualitative approach. Researchers chose three students in class VIII with different mathematical abilities (high, medium, and low) based on their value as research subjects. To collect data, researchers used ill-structured problem tests and interviews. The data were analyzed based on the level of students' creative thinking and follow-up interviews. The results showed that in aspect fluency, S1 and S2 could give two correct answers, while S3 only gave one correct answer. Aspects of flexibility: S1 and S2 can provide alternative answers using different mathematical concepts, while S3 only provides one way of providing alternative answers. Aspects of originality: S1 can provide two unique solutions, while S2 and S3 produce ordinary solutions. Based on this, S1 is included in level 4 (very creative), S2 is included in level 3 (creative), and S3 is included in level 0 (not creative). Based on the results of this study, designed learning must stimulate students' creative thinking abilities, such as by providing problem-solving questions that allow students to solve them with various strategies.